Brooke–Spiegler Syndrome in Japanese Siblings with an R758X Mutation: A Case Report - Takaya, Kento; Sakai, Shigeki; Kishi, Kazuo (Case reports in dermatology, 2025)
Introduction: Brooke-Spiegler syndrome is a rare hereditary skin disorder characterized by the development of multiple adnexal tumors, such as trichoepitheliomas and cylindromas, with a higher prevalence in females. Case Presentation: We report a rare case involving two male siblings who developed facial lesions consistent with this condition. Both patients presented with tumors on the nasal ala, which were successfully treated with carbon dioxide laser therapy. Genetic testing confirmed the diagnosis of Brooke-Spiegler syndrome, consistent with autosomal dominant inheritance. Conclusion: This case underscores the importance of family history and genetic evaluation in the diagnosis and management of this syndrome. Repeated CO₂ laser therapy may provide effective long-term cosmetic control of facial lesions.